Strengthening Fano resonance on gold nanoplates with gold nanospheres. Issue 3 (8th January 2020) - Cui, Ximin; Lai, Yunhe; Qin, Feng; Shao, Lei; Wang, Jianfang; Lin, Hai-Qing
Abstract : The silicon substrate-induced Fano resonance in Au nanoplates is strengthened by placing a gold nanosphere on the Au nanoplates. Abstract : Plasmonic Fano resonance has attracted extensive attention due to its many applications, including plasmonic sensing, electromagnetically induced transparency, light trapping and stopping, due to its narrow linewidth and asymmetric spectral shape. However, many metal nanostructures are designed with complex geometries to generate Fano resonance and few of them can support a deep Fano dip. Herein we report on the strengthening of the Fano resonance on silicon-supported Au nanoplates through the formation of (Au nanosphere)–(Au nanoplate) heterodimers. The deposition of the Au nanosphere on the top can greatly strengthen the substrate-induced Fano resonance of the Au nanoplate with a deep dip. We also observe that the replacement of the Au nanosphere with a Au nanocube can suppress the excitation of the Fano resonance in the heterodimer. When the sharp corners and edges of the nanocubes gradually become rounded, the Fano resonance appears again with increasing asymmetry. Both the dip depth and wavelength of the Fano resonance can be independently tailored by varying the nanosphere diameter and the nanoplate thickness, respectively. We believe that our results provide an attractive and facile platform for modulating Fano dips and constructing Fano resonance-based devices.